Perlindungan Hukum Terhadap Kebebasan Pers (Wartawan) Dalam Melakukan Kegiatan Jurnalistik - Nikodemus, Jimris Fantos; Latupeirissa, Julianus Edwin; Ubwarin, Erwin (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction:  Freedom of the press is fundamental. Freedom is meant in the context of exercising the rights, functions and roles of the press. Journalists as people who carry out these functions and roles, get guaranteed legal protection. In Article 8 of Law No. 40 of 1999 concerning the Press it states "In carrying out their profession journalists receive legal protection". However, in reality, cases of violence, intimidation and threats against journalists are still occurring.Purposes of the Research: Reviewing and discussing whether actions that impede freedom of the press can be held criminally responsible and reviewing and discussing legal protection for freedom of the press (journalists) in conducting journalistic activities.Methods of the Research: The research method used is normative research based on statutory approaches, case approaches and conceptual approaches.Results of the Research: The results of the research found that acts that impede freedom of the press (journalists) in carrying out journalistic activities are criminal acts and for those actions committed, they can be held criminally responsible and can be processed based on applicable law. On the other hand, legal protection from both the government and/or the public for journalists must be carried out with full awareness and a high sense of responsibility so that good synergy is built to create a sense of security for journalists in carrying out their noble duties.